Jobs in Global Value Chains - World Bank (World Bank, Washington, DC, 2017)
Participation in a Global Value Chain (GVC) can create more jobs through a structural transformation, and potential jobs spill overs from strengthened backward and forwardlinkages. GVCs can also have a positive impact on jobs for women. Evidence shows a disproportionateshare of jobs in labor-intensive chains benefiting women.Jobs in GVCs are better jobs because of higher wages and better working conditions, as domestic firms seek to comply with global standards to participate. However, these above mentioned labor market outcomes being achieved depend on several parameters, such as the sector of operations, level of firm operation, and existing distortionsin the labor market. But evidence for GVC participation leading to better jobs is strong at the firm level, given the win-win business case through higher productivity, efficiency, and profits.The jobs outcome through GVC participationcan be strengthened through focusing on GVC upgrading strategies, implementing and strengthening private standards, improving national regulations, and strengthening monitoring and evaluation of impact of GVC operations.